Detecção de trincas em aço do grau HP por correntes parasitas - Silva, Lucas Kling e (2018)
Steam reforming furnaces, where hydrogen is produced from hydrocarbons, are key to refining the production of the petroleum industry. These furnaces are composed of columns consisting of segments of HP austenitic steel tubes, where endothermic reactions of the refining process occur. However, premature failure can occur through creep damages leading to loss of production and unscheduled maintenance shutdowns. In this way, the challenge of detecting, monitoring and evaluating damage states and defects in this material is necessary. In this work, a non destructive test methodology was developed to detect cracks in different aging stages of HP austenitic steel. Through the development of probes of parasitic currents together with calibration and resultsoriented inspection process, a sample was detected in the operating sample of an HP tube segment, thus validating the methodology developed.